Point-of-Sale System at Bibingkinitan (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The system is entitled a point-of-sale at Bibingkinitan. A point-of-sale system helps a customer make payments to the merchant in exchange for goods and services. The current transactions that the company has been slow and unreliable. The company is using a manual transaction for their business. Hence, the business relies on its team’s capability to correctly calculate sales transactions, which can lead to mistakes and errors. This process can also be time-consuming. With this system, the company can easily make a computerized transaction without manually listing the name of the sold products and store in the inventory records. The proponents used the systems development life cycle as the guide in developing the system. As the proponents’ approach and methodology, the point of sale system flows in seven processes; after the researchers sought a client, they create plans and timelines for the proposed system. The proponents analyzed the collected data of the client’s problem for the features needed for the proposed system. The proponents created and developed an automated system that solved the client’s problem. The proponents conducted a seminar to those who will be possible users of the system created. The proponents checked the errors and bugs, as well as other defects, to verify whether the system operates correctly. The researchers developed the following features. The reporting feature gives an overview of the state of the sales activities within a company. This feature shows different trends happening in the sales volume over a certain time and also analyses various steps of the sales funnel and the performance of sales executives. The auto calculate feature allows the client to obtain a temporary result from a function without using a formula and calculator. The security feature prevents unauthorized intrusion into a premise, reports such attempts, and prevents unauthorized access. This feature will help the client to secure their records and have a safe and secured system. Point of sale system can improve the business transaction and process of the Bibingkinitan with their customers. With this system, the company can easily make a computerized transaction without manually listing the name of the sold products for inventory. From the manual process, this computerized system transforms the transaction into a modern way that will benefit the staff, especially the cashier, employees, customers, and the owner.
Keywords: point of sale system, bibingkinitan